ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU BERPRESTASI MENGGUNAKAN METODE ELECTRE PADA SMA ADHYAKSA 1 JAMBI - Mutawadiah; Jasmir; Joni Devitra (LPPM Universitas Dinamika Bangsa, 2024)
To improve the quality of education for students as the nation's next generation, teachers are needed who are competent in providing education to students. The main task of teachers is to educate, teach, guide, direct, train, assess and evaluate their students. Therefore, activities are held which aim to motivate teachers to improve their competence, one of which is a competition for selecting outstanding teachers. Meanwhile, the implementation of selecting outstanding teachers at SMA Adhyaksa 1 Jambi has not followed the proper procedures, where each teacher who will be selected must meet the assessment criteria that have been determined, such as pedagogical, personality, professional, social and performance that has been achieved. The obstacles faced in this assessment include the large number of criteria and participants. One method that is suitable in the process of selecting outstanding teachers is the Electre method because these criteria will be very relevant if the process of selecting outstanding teachers is used. The electre method is a multi-criteria decision making method based on the outranking concept by comparing alternatives and appropriate criteria in pairs. The aim to be achieved in this research is to carry out an analysis of the decision support system for selecting outstanding teachers at SMA Adhyaksa 1 Jambi.